Handling Compassion Fatigue in Complaint and Referral Unit Volunteers: Case Study of Komnas Perempuan (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
The spiking exposure of traumatic events faced by workers and volunteers in handling violence against women has the potential to lead to compassion fatigue. This research sought to describe the experience and protective factors of compassion fatigue in Complaint and Referral Unit volunteers who provide services to female victims of violence in Komnas Perempuan. A total of 3 respondents participated in this study through online interview. Thematic analysis is performed to analyze the data. The result suggested that the participants had compassion fatigue symptoms, which included burnout and secondary traumatic stress symptoms. The experience of burnout included physical and emotional exhaustion as well as guilt and helplessness. Whereas secondary traumatic stress was expressed in preoccupation of thoughts about victim’s violence case and projection in personal relationships. Nevertheless, these symptoms had been resolved due to protective factors such as personal characteristics (educational background and self-care) and social support (personal and professional support from the organization). This study added to our knowledge on how to create supportive system for volunters who provide services for victims of violence against women.